Conceptual Framework for A Perinatal Decision Support System using a Knowledge-Based Approach - Gunaratnam, Marry; Frize, Monique; Bariciak, Erika (CMBES Proceedings, 2012)
This paper discusses the development of a knowledge based perinatal clinical decision support system (CDSS) to predict preterm labour. It consists of a knowledge-base, a workflow engine, and a mechanism to communicate results. The knowledge base contains rules or associations related to the desired predictions; the workflow engine combines the rules in the knowledge base with the patient data; and the communication mechanism allows entry of the patient data into the system, and output of results in the form of notifications, alerts or emails. This system will help physicians to inform families and to initiate preventative care, monitoring, and treatment. The final form of the CDSS is to be integrated to an electronic medical record (EMR) and thus allow for auto-population of the patient data into appropriate fields. A web-based collaborative platform that meets the legal and regulatory accreditation standards will be used to deliver information relevant to clinical users.